Answer:
[tex]y = -\frac{1}{3}x + 3[/tex]
Step-by-step explanation:
Required
The graph equation
From the graph, we have:
[tex](x_1,y_1) = (0,3)[/tex]
[tex](x_2,y_2) = (3,2)[/tex]
First, calculate the slope (m)
[tex]m = \frac{y_2 -y_1}{x_2 -x_1}[/tex]
So, we have:
[tex]m = \frac{2-3}{3-0}[/tex]
[tex]m = \frac{-1}{3}[/tex]
[tex]m = -\frac{1}{3}[/tex]
The equation is calculated as:
[tex]y = m(x - x_1) + y_1[/tex]
This gives:
[tex]y = -\frac{1}{3}(x - 0) + 3[/tex]
[tex]y = -\frac{1}{3}(x) + 3[/tex]
[tex]y = -\frac{1}{3}x + 3[/tex]